Contribuições para determinação do incremento dos níveis de ruído devido a sonorizadores transversais em vias urbanas - Rolim, Ieure Amaral (2011)
Rumble strips are physical devices used for road safety. However, the noise emission generated during their operation compromises sound quality of the surrounding environment and disturbs neighborhood residents. That generates conflicts for local managers and authorities. This study aims to determine the increase in noise produced by Brazilian standard rumble strips in relation to traffic sound intensity levels in dB (A), as well as stablishing if the increase meets the sound intensity levels adopted as criteria by national legislation. Measurements of sound pressure levels in dB (A) were recorded in tests performed in a pilot test field installed at Federal University of Paraíba. In the tests, several types of vehicles at known speeds were used, with and without a rumble strip. A procedure was developed through the individual passage of each vehicle belonging to the three adopted classes (light, saloon and heavy vehicles) without rumble strips. After that, a noise prediction model was structured. The developed model is capable of estimating the sound pressure level in dB (A) for a known traffic composition easily found in circulation on urban roads. Besides, it can calculate the noise increment in dB (A) when Brazilian standard rumble strips are installed in the road. In order to evaluate the reliability of the model, six models available in the literature were selected: Kinsler et al. (1982), HMSO (1988), Celenk et al. (1997), Calixto et al. (2001), Pamanikabud et al. (2002), Tansatcha et al. (2005). To calibrate the model, 03 urban roads of João Pessoa were selected. It was proved that the developed model’s results were very close to those of Kinsler and HMSO models; as a result, the increase in sound pressure level caused by Brazilian standard rumble strips was calculated, resulting in values above 6 dB (A) at the surrounding area. This study may be useful in filling some gaps of current legislation, such as the determination of a distance that buildings should remain from rumble strips without being exposed to noise disturbances. Therefore, this study adds to the construction of a sustainable model of urban traffic management, considering the identification of traffic corridors responsible for changing the sound quality of urban environment.